Identification of barriers and facilitators for optimal cesarean section care: perspective of professionals - Sonja Melman; Rachel Hellen Petra Schreurs; Carmen Desiree Dirksen; Anneke Kwee; Jan Gerrit Nijhuis; Nicol Anna Cornelia Smeets; Hubertina Catharina Johanna Scheepers; Rosella Petronella Maria Gemma Hermens (BMC, 2017)
Abstract Background The cesarean section (CS) rate has increased over recent decades with poor guideline adherence as a possible cause. The objective of this study was to explore barriers and facilitators for delivering optimal care as described in clinical practice guidelines. Methods Key recommendations from evidence-based guidelines were used as a base to explore barriers and facilitators for delivering optimal CS care in The Netherlands. Both focus group and telephone interviews among 29 different obstetrical professionals were performed. Transcripts from the interviews were analysed. Barriers and facilitators were identified and categorised in six domains according to the framework developed by Grol: the guideline recommendations (I), the professional (II), the patient (III), the social context (IV), the organizational context (V) and the financial/legislation context (VI). Results Most barriers were found in the professional and organizational domain. Barriers mentioned by healthcare professionals were disagreement with specific guideline recommendations, and hesitation to allow women to be part of the decision making process. Other barriers are lack of adequately trained personal staff, lack of collaboration between professionals, and lack of technical equipment. Conclusions Clear facilitators and barriers for guideline adherence were identified in all domains. Several barriers may be addressed by using decision aids on mode of birth or prediction models to individualise care in women in whom both planned vaginal birth and CS are equal options. In women with an intended vaginal birth, adequate staffing and the availability of both fetal blood sampling and epidural analgesia are important.